Synthesis of porous silica materials with tunable morphologies and nanopore sizes using heterogemini surfactants. (1st May 2018) - Wu, Xuanxian; Yi, Sili; Li, Shuolin; Hou, Linxi
Abstract : A series of heterogemini surfactants C16 H33 OCH2 CH(OH)CH2 N + (CH3 )2 C n H2 n +1 ·Br – were used as the template to synthesise porous silica materials via a Stöber method. The influence of the alkyl chain length of heterogemini surfactants on the morphology of porous silica materials was studied. Porous silica materials were characterised by scanning electron microscopy, transmission electron microscopy and nitrogen adsorption–desorption analysis. Results showed that with the increase of alkyl chain length, the morphologies of porous silica materials gradually transform from sphere to sphere with cavity, sphere composed of vesicles, coral like and finally to lamella. Pore size of materials ranges from 1.17 to 3.93 nm. When the alkyl chain is short enough ( n = 8 and 10), a hierarchical pore size distribution can be obtained. The possible formation mechanism of the porous silica materials has been discussed.